A critical review in recent developments of metal-organic-frameworks (MOFs) with band engineering alteration for photocatalytic CO2 reduction to solar fuels. Issue 43 (January 2021) - Ikreedeegh, Riyadh Ramadhan; Tahir, Muhammad
Graphical abstract: Highlights: Recent developments in metal-organic framework (MOF) materials for photocatalytic CO2 reduction. General fundamentals of CO2 reduction including thermodynamics, mass transfer and mechanisms discussed. Advances in charge transfer mechanisms and heterojunctions are demonstrated. Synthesis methods for fabrication metal-organic framework (MOF) materials are discussed. Abstract: Photocatalytic CO2 reduction into valuable chemicals and fuels using solar energy is an attractive approach to solve environmental pollution caused by the emissions of greenhouse gases (mainly CO2 ) and the fossil fuels depletion. Photocatalysis has been recognized as a solar fuel production system due to its prospective applications in both reducing carbon dioxide emissions and producing of valuable chemicals under solar light. Recently, new, low-cost, crystalline porous materials known as metal-organic frameworks (MOFs) have been introduced as photocatalysts. However, they still face some challenges in terms of synthesis, sunlight utilization and some difficulties in understanding the structure–activity relationship. In this work, recent developments of metal-organic frameworks (MOFs) as a photocatalyst owing to their promising photochemical and unique textural properties for photocatalytic CO2 reduction has been explored. The main objective is to explore the main fundamentals such as the principle, thermodynamics and the mechanism including the heterostructures of charges transfer.The mass transfer theory for photocatalytic CO2 reduction have also been clearly deliberated. The recent developments in synthesis and classifications of MOF-based photocatalysts for increasing the photocatalytic CO2 conversion are discussed in details. Finally, future perspectives of MOF-assisted photocatalytic CO2 reduction have been suggested to provide an insight and important step forward to enhance efficiency with an economic and environmentally sustainable system.